2020
DOI: 10.1175/mwr-d-19-0023.1
|View full text |Cite
|
Sign up to set email alerts
|

How Significant are Low-Level Flow Patterns in Tropical Cyclone Genesis over the Western North Pacific?

Abstract: The low-level flow pattern characteristics of the tropical cyclone genesis (TCG) environment over the western North Pacific (WNP) were investigated not only for the periods during which TCG occurred, but also for the periods during which no TCG occurred. The flow patterns investigated were the shear line (SL), confluence region (CR), and easterly wave (EW) patterns. Although these flow patterns are recognized as favorable environmental conditions for TCG, their general characteristics, such as the climatologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Indeed, Fudeyasu and Yoshida (2019) showed that the number of TC geneses from the upper tropospheric cold lows is the highest in August. Yoshida and Fudeyasu (2020) found that the frequency of the easterly wave flow pattern, which often transforms into tropical depressions, is the highest in October. Considering the small number of tropical disturbances that transform into TCs, we need to understand how the activity of seeds of TC and their survival rate (the fraction of TC formation to tropical disturbances; Lee et al., 2020; Sugi et al., 2020; Yamada et al., 2021) are modulated by the BSISO and improve the model performance of TC genesis predictions based on this understanding.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Indeed, Fudeyasu and Yoshida (2019) showed that the number of TC geneses from the upper tropospheric cold lows is the highest in August. Yoshida and Fudeyasu (2020) found that the frequency of the easterly wave flow pattern, which often transforms into tropical depressions, is the highest in October. Considering the small number of tropical disturbances that transform into TCs, we need to understand how the activity of seeds of TC and their survival rate (the fraction of TC formation to tropical disturbances; Lee et al., 2020; Sugi et al., 2020; Yamada et al., 2021) are modulated by the BSISO and improve the model performance of TC genesis predictions based on this understanding.…”
Section: Summary and Discussionmentioning
confidence: 99%